The Post-Natal Development of Intraocular Pressure in Normal Domestic Cats (Felis catus) and in Feline Congenital Glaucoma - Adelman, Sara (Exp Eye Res, 2017)
Intraocular pressure (IOP) is the most consistent risk factor for progressive vision loss in glaucoma. Cats with recessively inherited feline congenital glaucoma (FCG) exhibit elevated IOP with gradual, painless progression of glaucoma similar to humans and are studied as a model of glaucoma in humans and animals. Here, post-natal development of IOP was characterized in normal domestic cats and in cats with FCG caused by a homozygous LTBP2 mutation. Rebound tonometry (TonoVet®, ICare Oy, Finland) was used to measure IOP non-invasively, 2–3 times weekly in 63 FCG and 33 normal kittens, of both sexes, from eyelid opening until 3–6 months of age. IOPs in the left and right eyes of both FCG and normal kittens were compared by paired t-test and linear regression. One-way ANOVA and Tukey-Kramer post-tests were used to compare IOP of cats grouped by age and disease status. A p-value <0.05 was considered significant. In the second week of life, mean IOP was 7.16 mmHg (SD=1.3) in normal kittens and 8.72 mmHg (SD=1.4) in kittens with FCG. Mean IOP at age 10 weeks was significantly higher in FCG (19.8 mmHg; 95% CI= 17.7, 21.9mmHg) than in normal kittens (13.2 mmHg; 95% CI= 11.9, 14.5mmHg). At 3 months of age, IOP in normal cats reached adult values while IOP in FCG cats continued to increase through at least six months of age. These results provide ranges for normal IOP values in young kittens and confirm that IOP is significantly higher than normal by 10wks of age in this spontaneous feline glaucoma model.